The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1074/jbc.m512935200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of a Mutation in an Expressed Human α-Cardiac Actin at a Site Implicated in Familial Hypertrophic Cardiomyopathy

Abstract: Point mutations in human ␣-cardiac actin cause familial hypertrophic cardiomyopathy. Functional characterization of these actin mutants has been limited by the lack of a high level expression system for human cardiac actin. Here, wild-type (WT) human ␣-cardiac actin and a mutant E99K actin have been expressed and purified from the baculovirus/insect cell expression system. Glu-99 in subdomain 1 of actin is thought to interact with a positively charged cluster located in the lower 50-kDa domain of the myosin mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 34 publications
2
59
1
Order By: Relevance
“…The acto-S1 docking model (50) suggests that Arg-95 of actin is involved in the interaction with myosin, and previous mutational studies suggest that negative charges in this region are important for myosin binding (48,(51)(52)(53). Consistent with this, R95C filaments, in which the net negative charge is increased in the region, showed greater affinity for myosin in in vitro motility assays.…”
Section: Velocitysupporting
confidence: 70%
“…The acto-S1 docking model (50) suggests that Arg-95 of actin is involved in the interaction with myosin, and previous mutational studies suggest that negative charges in this region are important for myosin binding (48,(51)(52)(53). Consistent with this, R95C filaments, in which the net negative charge is increased in the region, showed greater affinity for myosin in in vitro motility assays.…”
Section: Velocitysupporting
confidence: 70%
“…This study also revealed reduced thin filament cooperativity; this may influence Ca 2ϩ sensitivity under some conditions, although our previous analysis of tropomyosin DCM mutations found no connection between cooperativity and phenotype (23). Studies on the kinetics of baculovirus-expressed E99K actin-activated myosin S-1-ATPase show that the K m is 4-fold greater than wild type, indicating a weakening of the weak binding interaction between actin and myosin⅐ADP⅐P i (45). This was interpreted as leading to lower force production, but we found the maximum developed pressure in ACTC E99K hearts was not different from nontransgenic mice.…”
Section: Actc E99k Mouse Model Of Hcm-we Developed Thementioning
confidence: 99%
“…Other actin mutations within myosin binding domains (e.g., A331P and A295S) are associated with HCM. One actin HCM mutation (E99K) has been evaluated in vitro by a series of biochemical assays, which demonstrated a weakened interaction with myosin and reduced force production (73). Several other actin mutations have been expressed in vitro and found to demonstrate variable defects in protein folding which correlated with impaired incorporation into the cytoskeleton of mammalian (noncardiac) cell lines (919).…”
Section: Actinmentioning
confidence: 99%